2010
DOI: 10.1586/eop.10.52
|View full text |Cite
|
Sign up to set email alerts
|

Severe bacterial endophthalmitis: towards improving clinical outcomes

Abstract: Endophthalmitis is an infection and inflammation of the interior of the eye that can result in significant vision loss. This infection occurs as a result of the seeding of organisms into the interior of the eye following surgery (postoperative), trauma (post-traumatic) or an infection in another site in the body (endogenous). The general rate of endophthalmitis has remained steady over the past several years. However, the increased use of intraocular injections to treat various degenerative and inflammatory oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 96 publications
(97 reference statements)
1
40
0
9
Order By: Relevance
“…(30,31) The course of endophthalmitis, treatment effectiveness and visual outcome can be unpredictable. (33) Clinical presentation of the disease depends, in part, on the relative virulence of the infecting pathogen, the mechanism of introduction into the eye and how quickly treatment is initiated. (33) Other factors that affect the outcome of infection include the patients' age, how vulnerable the infecting agent is to antibiotic therapy and the anatomic condition of the eye during infection.…”
Section: Pathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…(30,31) The course of endophthalmitis, treatment effectiveness and visual outcome can be unpredictable. (33) Clinical presentation of the disease depends, in part, on the relative virulence of the infecting pathogen, the mechanism of introduction into the eye and how quickly treatment is initiated. (33) Other factors that affect the outcome of infection include the patients' age, how vulnerable the infecting agent is to antibiotic therapy and the anatomic condition of the eye during infection.…”
Section: Pathogenesismentioning
confidence: 99%
“…(33) Clinical presentation of the disease depends, in part, on the relative virulence of the infecting pathogen, the mechanism of introduction into the eye and how quickly treatment is initiated. (33) Other factors that affect the outcome of infection include the patients' age, how vulnerable the infecting agent is to antibiotic therapy and the anatomic condition of the eye during infection. (33) Clinical studies have reported that increased time between infection and treatment is associated with a worse visual outcome.…”
Section: Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations